Clinic Care Information System (CCS) / Lee Mei Koon - Lee , Mei Koon (2003)
The purpose of this study is to develop a clinic management system used for clinic in Malaysia. A main objective is to provide services including manage patient records, manage medicine stocks and produce management reports. System will reduce processing steps, lessen the use of papers and help staff to search the information with less time. The system is developed on a window platform. A Microsoft Access database management system is used. Visual Basic 6.0 is used as a software tool for development. Two-tiered client server architecture is used to support the Clinic Care Information System (CCS). Waterfall model of the Software Development Life Cycle is employed in the development of this system.